2003
DOI: 10.1080/0075417031000138442
|View full text |Cite
|
Sign up to set email alerts
|

Attachment representations and adoption: associations between maternal states of mind and emotion narratives in previously maltreated children

Abstract: This paper reports on associations observed between Adult Attachment Interviews (AAIs) obtained from adoptive mothers, and emotional themes appearing in doll play narratives obtained from their recently adopted children. The children, aged 4 -8 years, carried into their adoptive placements a history of consistently serious maltreatment, including neglect and abuse. Results reveal strong and significant influences of maternal state of mind regarding attachment upon their adopted children's storycompletions. Mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
92
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(102 citation statements)
references
References 28 publications
6
92
1
1
Order By: Relevance
“…As in the case of abandonment, research findings confirm a positive correlation between maltreatment and the failure of affected children to attach securely to subsequent carers (Howe, 2005;Kobak & Madsen, 2008;Mennen & O'Keefe, 2005;Prior & Glaser, 2006;Steele, Hodges, Kaniuk, Hillman & Enderson, 2003;Wilson, 2009). For example, in a meta-analysis of 13 studies, Morton andBrowne (1998 in Mennen &O'Keefe, 2005) discovered that maltreated children in 11 of the 13 studies were more insecurely attached compared to control group children.…”
Section: Risks Associated With Child Abandonmentmentioning
confidence: 62%
See 1 more Smart Citation
“…As in the case of abandonment, research findings confirm a positive correlation between maltreatment and the failure of affected children to attach securely to subsequent carers (Howe, 2005;Kobak & Madsen, 2008;Mennen & O'Keefe, 2005;Prior & Glaser, 2006;Steele, Hodges, Kaniuk, Hillman & Enderson, 2003;Wilson, 2009). For example, in a meta-analysis of 13 studies, Morton andBrowne (1998 in Mennen &O'Keefe, 2005) discovered that maltreated children in 11 of the 13 studies were more insecurely attached compared to control group children.…”
Section: Risks Associated With Child Abandonmentmentioning
confidence: 62%
“…Intergenerational progression of maltreatment has also been noted among families with maltreating histories (e.g. Morton & Brown, 1998in Mennen & O'Keefe, 2005Steele et al, 2003). A study by Van den Dries, Juffer, Ijzendoorn and BakermansKranenburg (2009) further found that maltreatment has a negative correlation with academic performance.…”
Section: Risks Associated With Child Abandonmentmentioning
confidence: 92%
“…Outra proposta defendida por Bowlby prende-se com as situações em que a figura de vinculação apresenta comportamentos marcadamente contraditórios, o que leva a que a criança desenvolva diferentes tipos de representações em relação a essa figura (Steele, Hodges, Kaniuk, Hillman & Henderson, 2003). Contudo, Bowlby considera, ainda, que os pais têm um papel facilitador em auxiliar os seus filhos na construção e revisão dos modelos dinâmicos através do diálogo.…”
Section: Os Modelos Internos Na Idade Do Pré-escolarunclassified
“…The adoptive parents might have difficulty attaching to an older child, who may be traumatised, sad or angry. The adoptive parents might also interfere with a normal attachment process due to their own specific traumas, grief and inabilities to attach [28][29][30][31][32]50]. This is a difficult situation and can require professional help to resolve, and is a reason why adoptive parents are now included in the search for criteria affecting the attachment process.…”
Section: Think I Am Familymentioning
confidence: 99%
“…When applied to adoption, the focus moved from solely concerning the adoptee to now including the adoptive mother and her ability for normal attachment behaviour [6,[28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%